The Present Situation of Travel Agencies and Their Future Prospects in Bhutan / Tashi Dorji and Manat Chaisawat - Dorji, Tashi; Chaisawat, Manat (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
Since the inception of tourism in 1974, Bhutan has been guided by the policy of cautious growth, a "High Value, and Low Impact" principle. With the increase in the international tourist arrivals, the role and responsibility of travel agents have become more intense and challenging. The researcher aims to provide a better understanding of the current working situation of the travel agencies, the major trends affecting their roles, and finally to propose a guideline for future development of travel agents in Bhutan. The convenience sampling method was used for both the distribution of questionnaires to the tourists at the Paro International Airport and also for semi-structured interviews conducted with the travel agents and the Association of Bhutanese Tour Operators. The findings of the study indicated that the majority of the international tourists to Bhutan were senior citizens with high income levels and were first time visitors. The respondents were very satisfied with the overall performance of the travel agents. However, the findings indicated that travel agents in Bhutan did not perform to the high level of the service quality attributes perceived by the tourists. It is recommended that the travel agents, other tourism stakeholders and the government should work together in allocating the resources effectively and focus more on enhancing the quality of service attributes to maintain and maximize guest satisfaction. Furthermore, travel agents need to intensively emphasize the use of ICT as a marketing and promotional tool for its products and services to reach the international markets.